1980
DOI: 10.5951/jresematheduc.11.5.0356
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in High School Students' Causal Attributions of Performance in Mathematics

Abstract: The theory of causal attribution was applied to the problem of mathematics avoidance or the under-enrollment of females in nonrequired high school mathematics courses. It was hypothesized that sex differences in attributions of performance in mathematics would parallel previously documented sex differences in attributions in other achievement areas. Twelve hundred and twenty-four high school females (N=647) and males (N=577) took the Mathematics Attribution Scale and a test of mathematics achievement. As predi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
1
1

Year Published

1982
1982
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 8 publications
2
11
1
1
Order By: Relevance
“…On the contrary, our data differ from those obtained by Wolleat et al (1980). They found that girls explained their success as due to their effort, while boys explained it on the basis of their ability.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…On the contrary, our data differ from those obtained by Wolleat et al (1980). They found that girls explained their success as due to their effort, while boys explained it on the basis of their ability.…”
Section: Discussioncontrasting
confidence: 99%
“…The work of Callahan (1971) marked the beginning of the growth of concern about pupils' attitudes with respect to mathematics. Examples of the subsequent work on attitudes towards mathematics are Sherman (1976, 1978), Whitley (1979), Wolleat, Ponte, Becker and Fennema (1980), Hannafin (1981), Schofield (1982), Haladyna, Shaughnessy and Shaughnessy (1983), Minato (1983), Smith (1985), Gairín (1990), Mohd Yusof (1994, Camacho, Hernández and Socas (1995), Carbonero Martin, Antón Martin and Arranz Espeso (1998), Hernández and Socas (1999), Hernández, Palarea and Socas (2001), and Cubillo and Ortega (2002).…”
Section: Introductionmentioning
confidence: 99%
“…Fennema (Fennema, Wolleat, & Pedro, 1979; see also Wolleat et al, 1980) used Weiner's earlier model as the basis of a selfattribution scale for mathematics performance. She argued for the separation of success and failure and also expanded the luck category to include a wider range of unstable, external causes that she called "environment."…”
Section: Dimensions Of Perceived Causes For Academic Outcomesmentioning
confidence: 99%
“…Regarding the role of gender, Wolleat et al (1980) found that the attributions made by men for success in mathematics corresponded to ability, whereas women attributed their successes more to effort. Barrett (1987, as cited in Higgins andLaPointe, 2012) found that first-year college students who made internal, stable, and global attributions for failure are at risk for poor grades.…”
Section: Introductionmentioning
confidence: 99%